KAJIAN PEMANFAATAN RUANG TERHADAP SISTEM LAHAN PERMUKIMAN DALAM RENCANA TATA RUANG WILAYAH DIKAWASAN KECAMATAN BATANG KUIS KABUPATEN DELI SERDANG - Dimas Setiawan; Wahyu Hidayat; Abdiyanto Abdiyanto (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The form of using space as residential land is a form of expression of human activities that use space as a place to live. This study aims to determine the level of suitability of space utilization and to determine the use of space for residential land systems in the Regional Spatial Plan (RTRW) in the Batang Kuis sub-district area. The method used in this study is a qualitative method with a descriptive approach. Data collection techniques are in the form of observation, interviews and documentation. The results showed that the level of suitability of space use in general was quite good, with about 90% of the area having complied with the stipulated provisions. The Regional Spatial Plan (RTRW) policy has become an effective guide for developers in planning the development of residential areas. The use of space for residential land systems in the Regional Spatial Plan in the Batang Kuis District area shows the importance of the Regional Spatial Plan policy in directing regional development in a planned and sustainable manner. Of the total area of 40.34 km², most of the land, which is 38.14 km², has been appropriately used as residential areas. However, there are still 2.20 km² of land that has been converted without being appropriated, often in the form of productive land such as rice fields and fields. Keywords: Batang Kuis District; Land; Regional Spatial Plan; Spatial Utilization  Abstrak: Bentuk pemanfaatan ruang sebagai lahan pemukiman merupakan bentuk ekspresi aktivitas manusia yang menggunakan ruang sebagai tempat tinggal. Penelitian ini bertujuan untuk mengetahui tingkat kesesuaian pemanfaatan ruang dan untuk mengetahui pemanfaatan ruang terhadap sistem lahan permukiman dalam Rencana Tata Ruang Wilayah (RTRW) dikawasan kecamatan Batang Kuis. Metode yang digunakan dalam penelitian ini yaitu metode kualitataif dengan pendekatan deskriptif. Teknik pengumpulan data berupa observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa tingkat kesesuaian pemanfaatan ruang secara umum cukup baik, dengan sekitar 90% wilayah telah mematuhi ketentuan yang ditetapkan. Kebijakan Rencana Tata Ruang Wilayah (RTRW) telah menjadi panduan yang efektif bagi para pengembang dalam merencanakan pembangunan kawasan permukiman. Pemanfaatan ruang terhadap sistem lahan permukiman dalam Rencana Tata Ruang Wilayah dikawasan Kecamatan Batang Kuis menunjukkan pentingnya kebijakan Rencana Tata Ruang Wilayah dalam mengarahkan pengembangan kawasan secara terencana dan berkelanjutan. Dari total luas wilayah sebesar 40,34 km², sebagian besar lahan, yaitu 38,14 km², telah dimanfaatkan secara sesuai sebagai kawasan permukiman. Namun, masih terdapat 2,20 km² lahan yang dialihfungsikan tanpa sesuai dengan peruntukannya, sering kali berupa lahan produktif seperti sawah dan ladang.Kata Kunci: Pemanfaatan Ruang; Lahan, Rencana Tata Ruang Wilayah;, Kecamatan Batang Kuis